RESEARCH INTO THE QUALITY AND SAFETY OF TABLE LINEN FOR THE HOSPITALITY INDUSTRY - KALASHNYK, OLENA; PELYK, LESYA; KIRYCHENKO, OLENA; BUDNYK, NINA; MOROZ, SVETLANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Table linen, as an important element of the interior, adds comfort, aesthetics and elegance, must meet high standards of hospitality, ensure hygiene and safety of consumption, be durable, etc. That is, table linen is an indicator of quality and safety of service. This article highlights the issue of research into the quality and safety of such a frequently used element of the table linen assortment as napkins of Ukrainian production. In the process of research, the components of the raw material composition of napkins were identified and attributed to the group "semi-linen". It was found that the surface density is 211. g/m2, the specific breaking load on the warp is 253, on the weft - 217 N×m/g; breaking force per thread on the warp is 4.5 N, on the weft - 2.4 N; relative elongation at the moment of breaking on the warp is 15%, on the weft is 18%. Napkin samples by the coefficient of non-shrinkage, with indicators on the basis of 38%, weft - 36%, are classified as a group of low non-shrinkage. Safety indicators were also measured, namely the pH value of the water extract, the content of pesticides, the maximum permissible levels of toxic elements (lead, cadmium, arsenic, cobalt, nickel, chromium, copper), which met the requirements of regulatory documentation. Therefore, Ukrainian-made half-linen napkins are high-quality and safe, they can be used in the hospitality industry. Studies of the safety indicators of samples of Ukrainian-made semi-linen napkins showed compliance with the requirements of the national standard and OEKO-TEX® STANDARD 100 in terms of pH level, content of pesticides and extractable heavy metals. This proves the responsibility of the napkin manufacturer and makes them safe for operation and the environment. The choice of high-quality, durable, safe, environmentally friendly textile products contributes to the reduction of waste and natural resources.